Politeness strategies in English conversation: A pragmatic perspective - Farhan Salim; Genkateswarlu Dripathi; Xavier Mehayov (Journal of Research in English Language Teaching and Linguistics, 2025)
This study investigates the use of politeness strategies in spontaneous English conversations, addressing a significant gap in the literature where insights are predominantly drawn from scripted data. While existing research has explored how politeness functions in educational and intercultural contexts, there remains a lack of empirical evidence on real-life interactions that incorporate diverse speaker identities and contexts. The primary aim of this research is to identify and analyze the frequency and distribution of politeness strategies across various interactional settings, with particular attention to the differences between native and non-native speakers and the influence of gender. The research design employed a mixed-methods approach featuring 40 participants from different backgrounds, including both native and non-native English speakers. The study employed a triangulated set of instruments including audio recording devices to capture authentic spoken interactions, a structured Participant Profile Questionnaire to gather demographic data, and a detailed coding framework based on Brown and Levinson’s politeness theory for analyzing politeness strategies. The analysis utilized quantitative methods to code the politeness strategies identified within the conversations and qualitative discourse analysis to interpret these strategies in context. Findings revealed a predominance of positive politeness in peer-to-peer interactions, highlighting the role of relationship-building and social closeness, while negative politeness was prevalent in formal student-teacher exchanges, reflecting an emphasis on respect and deference. Notably, the analysis also showed that gender differences influenced the choice and frequency of politeness strategies, with women often employing more accommodating approaches. This study enriches the understanding of how politeness strategies are contextually employed in English conversations and underscores the need for integrating pragmatic competence into language education. The implications suggest that enhancing awareness and understanding of politeness strategies can significantly improve communicative competence in multicultural and multilingual contexts, benefiting both learners and educators alike.